NATURALIZED PSYCHOLOGY AS NEUROPHYOLOSPHICAL AND NEUROEPISTEMOLOGICAL TOOL. - Paul Ruiz (CAEN, 2010)
This paper tries to explain the link between biology and psychology, using psychosomatic and cognitive neurosciences as binding bridges. It is possible to build these bridges through the naturalization of psychological processes linking them to different biological processes. The paper does not intend to seal psychological processes through their simplification and reductionism. Instead, it seeks to reach the implicit consequences of the bond between psychosomatic, cognitive processes and the body dialectically, using the naturalization process as a tool for this.